'Where have all the doctors gone?' A protocol for an ethnographic study of the retention problem in emergency medicine in the UK. Issue 11 (30th November 2020) - Darbyshire, Daniel; Brewster, Liz; Isba, Rachel; Body, Richard; Goodwin, Dawn
Abstract : Introduction: 'Emergency medicine (EM) in the UK has a medical staffing crisis.' Inadequate staffing, in EM and across healthcare, is a problem that affects the quality of patient care globally. Retention of doctors in EM is a particularly acute problem in the UK's National Health Service. Sustainable careers in healthcare are gaining increasing attention at a national and international policy level, but research to understand the factors that facilitate retention is lacking. This study aims to develop understanding of what drives retention of doctors in EM by focusing on those who remain in these careers, where previous research has targeted those who have left. By addressing the problem of retention in a different way, using innovative methods in this context, we aim to develop a deeper and more nuanced understanding of sustainable careers in EM. Methods and analysis: This is an ethnographic study combining participant observation in two emergency departments, interviews with doctors from these departments, from organisations with influence or interest at a policy level and with doctors who have left EM. The analyses will integrate detailed workplace observation alongside key academic and policy documents using reflexive thematic analysis. Ethics and dissemination: Approvals have been obtained from Lancaster University via the Faculty of Health and Medicine Research Ethics Committee (FHMREC18058) and the Health Research Authority (IRAS number 256306). The findings will inform understanding of sustainable careers in EM that may be transferable to other settings, professions, and locations that share key characteristics with EM such as paediatrics, emergency nursing and general practice. Findings will be disseminated through a series of academic publications and presentations, through local and specialty research engagement, and through targeted policy statements.